An [O iii] search for extended emission around AGN with H i mapping: a distant cloud ionized by Mkn 1. Issue 2 (2nd June 2020) - Knese, Erin Darnell; Keel, William C; Knese, Greg; Bennert, Vardha N; Moiseev, Alexei; Grokhovskaya, Aleksandra; Dodonov, Sergei N
ABSTRACT: Motivated by the discovery of large ionized clouds around AGN, and particularly the large fraction of those that are consistent with photoionized gaseous tidal debris, we searched for [O iii ] emission around Seyfert galaxies previously mapped in H i, many with extended gas features. Of 26 Seyfert galaxies, we find one spatially extended emission feature, a discrete cloud projected ≈12 kpc SW from the centre of Mkn 1 and spanning a transverse extent of 8 kpc. Optical spectroscopy (Kast/Lick and SCORPIO/BTA) of this cloud confirms its association with the Mkn 1–NGC 451 galaxy pair, closely matching the kinematics of nearby H i structures, and reveals emission-line ratios requiring photoionization by the AGN at roughly the direct observed luminosity of the nucleus. For the entire sample, the full opening angle of the ionization cones (bicones) must be <20° if the AGNs are continuously bright for scales longer than the light-traveltimes to the H i structures. Since typical AGN ionization cones are observed to be much broader than this, our low detection fraction may add to evidence for the ubiquity of strong variations in AGN luminosity on scales 10 4 –10 5 yr.